Ungarn 1944-1945 - Fritz, Regina 1980- (Die Verfolgung und Ermordung der europäischen Juden durch das nationalsozialistische Deutschland 1933-1945, 2021)
As military defeat loomed large, Nazi Germany occupied Hungary. Immediately, the Nazis began the deportation of Jews living under Hungarian rule. The volume documents the fate of over 700,000 persons, from the First Anti-Jewish Law in 1938 to the radicalization of persecution under German occupation